Efektivitas Edukasi Berbasis Sekolah dengan Demonstrasi Pemeriksaan NS1 terhadap Peningkatan Literasi Kesehatan Demam Berdarah Dengue pada Siswa SMK Siere Cendikia Tangerang - Aruan, Maroloan; Meriyantia, Tandry; Chrisantya Vinna Tahalele; Hulda Baba; Virginia Ludji; Resky Sanda; Agamonanza, Freddy (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Banten Province. Low knowledge among adolescents increases transmission risks in schools and households. This community service aims to improve DHF knowledge among students at SMK Kesehatan Siere Cendikia Tangerang through school-based health education. The methods included interactive lectures, discussions, and NS1 antigen testing demonstrations for 38 students on May 31, 2024. Evaluation results showed a significant 28% increase in average knowledge, rising from 53% in the pre-test to 81% in the post-test. The most notable improvement occurred in understanding clinical phases and preventive measures. This activity effectively enhanced students' health literacy. Combining education with laboratory demonstrations potentially fosters preventive behavior and empowers students as agents of change in community DHF control.